Case Report: Congenital tuberculosis in an aborted dromedary camel fetus - Narnaware, Shirish Dadarao; Jyotsana, Basanti; Ranjan, Rakesh; Prakash, Ved; Choudhary, Shyam Sundar; Sahoo, Artabandhu (Frontiers in Veterinary Science, 2022)
Tuberculosis (TB) is a serious public health problem worldwide, especially in tropical developing countries. Nevertheless, reports on congenital TB in humans and animals are extremely rare. In this study, abortion was reported in an 8-year-old she-camel at the 9th month of gestation. The she-camel appeared healthy in clinical examination, had good body condition score, normal appetite, and had no signs of respiratory disease and fever. The expelled placenta was dark red-colored, thickened, and edematous with multifocal to coalescing ecchymotic hemorrhages on allantoic surface. The striking finding was multiple, white-yellow, solid nodular lesions in the fetal lung, pleura and liver. On histopathology, typical granulomatous lesions were detected in the lung and liver characterized by caseous necrosis surrounded by lymphocyte and macrophage infiltration, and concentric layers of fibrosis. The Ziehl-Neelsen staining detected scarce acid-fast bacilli in lung and liver tissues. The DNA extracted from tubercular lesions from lung and liver showed amplification of IS6110 region of Mycobacterium tuberculosis complex by PCR. The sequencing and phylogenetic analysis revealed close association of these sequences with Mycobacterium tuberculosis. The she-camel was detected positive for single intradermal tuberculin test performed 24 hours after abortion. This is the first report on congenital TB caused by M. tuberculosis in dromedary camel fetus with a possible vertical transmission.